ZaŽivljenje! - Klement, Blaž (knjige, 2024)
ForLife!: A Selection of Chapters on First Aid. ZaŽivljenje!; a selection of chapters on first aid is a professional monograph prepared by students for medica! students. It is intended as an aid to the education of first aid instructors and all others who are learning first aid. The selection of chapters covers the basic areas of first aid, such as: the ABCDE approach, the basic procedures of resuscitation (TPO) in the adult and in the child, the use of supplementary resuscitation procedures, immobilization and stopping bleeding.
Keywords: advanced cardiopulmonary resuscitation; automated external defibrillator (AED); avtomatski eksterni defibrilator (AED); cardiopulmonary resuscitation (CPR); dodatni postopki oživljanja (DPO); immobilisation; imobilizacija; stoping bleeding; temeljni postopki oživljanja (TPO); ustavljanje krvavitev